1987
DOI: 10.1177/088840648701000307
|View full text |Cite
|
Sign up to set email alerts
|

Content of Special Education Teacher Preparation

Abstract: This article represents an effort to examine the content of special education teacher-training programs in relationship to the changing role and function of special educators. This investigation involved a national survey of special education undergraduate and graduate programs on the relative amount of emphasis placed on (a) preschool, primary, adolescent, and adult populations and (b) 11 content areas. While the data reveal no significant differences with regard to the four pupil populations, rankings for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…These findings, hence, bear significant implications in order to enhance the quality of education in different disciplines. Considering that a limited number of teachers get training as consultants, collaborators, or team teachers at the in-service level (Gable, Young, & Hendrickson, 1987), their effectiveness may be vulnerable to the role they play and the context and the community in which they work, compared to the education they received (Allinder, 1994). The significance of adapting for teachers' needs, irrespective of the value placed by society of a particular discipline, should be underscored at all levels of pre-service and in-service education.…”
Section: Discussionmentioning
confidence: 99%
“…These findings, hence, bear significant implications in order to enhance the quality of education in different disciplines. Considering that a limited number of teachers get training as consultants, collaborators, or team teachers at the in-service level (Gable, Young, & Hendrickson, 1987), their effectiveness may be vulnerable to the role they play and the context and the community in which they work, compared to the education they received (Allinder, 1994). The significance of adapting for teachers' needs, irrespective of the value placed by society of a particular discipline, should be underscored at all levels of pre-service and in-service education.…”
Section: Discussionmentioning
confidence: 99%
“…These lists often are generated by polling teachers and experts from higher education (Ysseldyke & Algozzine, 1982). What has come to light is the apparent mismatch between coursework and what teachers need to know and be able to do to be effective in the classroom (Gable, Young, & Hendrickson, 1987). Knowledge of subject matter presented in didactic classes did not appear to be an adequate contributor or predictor of teacher competence (Menges, 1975).…”
Section: Performance-based Preservice Educationmentioning
confidence: 99%
“…Two recent national surveys revealed that preservice special education programs emphasize academic instruction, materials selection, management, and adaptation (Gable, Young, & Hendrickson, 1987) and direct instruction, task analysis, curriculum-based assessment, and applied behavioral analysis (Pugach & Whitten, 1987). Yet relatively little is known about the actual content of preservice preparation programs for teachers of mildly handicapped students.…”
mentioning
confidence: 99%